Chiral 3D Open‐Framework Material Ni(D‐cam)(H2O)2 Used as GC Stationary Phase. Issue 1 (8th November 2013) - Xie, Shengming; Wang, Bangjin; Zhang, Xinhuan; Zhang, Junhui; Zhang, Mei; Yuan, Liming
ABSTRACT Metal‐organic frameworks (MOFs) have been explored for analytical applications because of their outstanding properties such as high surface areas, flexibility and specific structure features, especially for chromatography application in recent years. In this work, a chiral MOF Ni(D‐cam)(H2O)2 with unusual integration of molecular chirality, absolute helicity, and 3‐D intrinsic chiral net was chosen as stationary phase to prepare Ni(D‐cam)(H2O)2‐coated open tubular columns for high‐resolution gas chromatographic (GC) separation. Two fused‐silica open tubular columns with different inner diameters and lengths, including column A (30 m × 250 µm i.d.) and column B (2 m × 75 µm i.d.), were prepared via a dynamic coating method. The chromatographic properties of the two columns were investigated using n‐dodecane as the analyte at 120 °C. The number of theoretical plates (plates/m) of the two metal–organic framework (MOF) columns was 1300 and 2750, respectively. The racemates, isomer and linear alkanes mixture were used as analytes for evaluating the separation properties of Ni(D‐cam)(H2O)2‐coated open tubular columns. The results showed that the columns offered good separations of isomer and linear alkanes mixture, especially racemates. Chirality 26:27–32, 2013. © 2013 Wiley Periodicals, Inc.